Prenatal Prediction of Difficult Intubation in Periviable Neonates Using Standard Fetal Biometric Parameters - Lynch, Tara A.; Glantz, J. Christopher; Drennan, Kathryn (American Journal of Perinatology, 2019)
Objective To assess whether standard fetal biometric parameters can be used to predict difficult intubations in periviable neonates undergoing resuscitation.Study Design This is a retrospective case–control study of periviable neonates delivered at 23 to 256/7 weeks at an academic hospital during a 5-year period in whom intubation was attempted. Standard fetal biometric measurements were included if they were taken within 7 days of delivery. Primary outcome was intubation in one attempt and was compared with more than one attempt. Data were also collected for fetal gestational age at delivery, neonatal birth weight, estimated fetal weight, head circumference, biparietal diameter, and abdominal circumference. Parametric and nonparametric statistical tests used p < 0.05 as significant.Results In total, 93 neonates met the inclusion criteria. The mean estimated fetal weight was 675 g (standard deviation [SD] ± 140), and the mean neonatal birth weight was 706 g (SD ± 151). The median interval between fetal ultrasound and delivery was 3 days (range: 0–7 days). A total of 45 neonates (48.3%) required more than one intubation attempt. The median number of intubation attempts was 1 (range: 1–10). There was no association between intubation difficulty and fetal abdominal circumference, biparietal diameter, head circumference, gestational age, estimated fetal weight, and neonatal birth weight (all p > 0.05).Conclusion Standard biometry in periviable neonates does not predict intubation difficulty.
Keywords: periviable; intubation; preterm birth; biometry